Politics, policies, and the effectiveness of foreign aid in fragile states - Matthew Kofi Ocran (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
International development cooperation has evolved since the 1960s. The effectiveness of aid is still topical, but studies have not paid adequate attention to the relationship between sectoral aid, politics, institutions, and aid effectiveness in fragile states. Using data from 2002 to 2020, this paper examines the effects of education aid and health aid on education outcomes and health outcomes in fragile states. It uses the Arellano-Bover/Blundell-Bond system generalized method of moments estimator to examine the effect of health aid and education aid on maternal mortality and primary school completion. There is evidence of muted effectiveness of health aid and education aid on health and education outcomes in the face of fragile contexts. There is ample evidence that policies and institutional factors matter for aid effectiveness. Donor support for social sectors in fragile states must be accompanied by support for institution-building and policy formulation processes.
Keywords: F34; F35; I20; O19; 330; aid effectiveness; education aid; health aid; maternal mortality; primary school completion; fragile states